2015
DOI: 10.1002/biof.1200
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 sensitizes prostate cancer cells to radiation via decreasing basal ROS levels

Abstract: Androgen deprivation therapy (ADT) was reported to lower basal ROS level in prostate cancer (PCa) and to sensitize PCa to radiation. We aimed to seek for the underlying molecular mechanism and to develop novel additive treatments to ADT in this regard. We simulated human androgen milieu in vitro and tested the ROS level in PCa cells undergoing ADT. We also tested the Nrf2 level in PCa cells with or without ADT. Genetic and pharmaceutical upregulation of Nrf2 was applied in vitro and in vivo in transgenic adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…Not surprisingly, previous studies also proved that Nrf2 plays a key role in the development of cancers [2830], including prostate cancer [19, 31]. It seems that an increased expression of Nrf2 may suppress the proliferation and invasion abilities of prostate cancer cells [19, 32], which exactly agreed with the results of our present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Not surprisingly, previous studies also proved that Nrf2 plays a key role in the development of cancers [2830], including prostate cancer [19, 31]. It seems that an increased expression of Nrf2 may suppress the proliferation and invasion abilities of prostate cancer cells [19, 32], which exactly agreed with the results of our present study.…”
Section: Discussionsupporting
confidence: 93%
“…Not surprisingly, previous studies also proved that Nrf2 plays a key role in the development of cancers [2830], including prostate cancer [19, 31]. It seems that an increased expression of Nrf2 may suppress the proliferation and invasion abilities of prostate cancer cells [19, 32], which exactly agreed with the results of our present study. However, Raatikainen et al revealed that when the Nrf2 was increased, the biochemical recurrence-free survival would be shortened and the overall survival rate would be worse, indicating a worse prognosis of prostate cancer patients and enhanced proliferative and invasive abilities [33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, reduced susceptibility to ROS-induced cellular damage and efficient repair of radiation-induced DNA damage was proposed as an underlying mechanisms to the observed radioresistance of prostate cancer stem cells 55 . Lower ROS basal levels were associated with increased Nfr2 levels and radiosensitivity in prostate cancer cells 56 . Basal ROS levels were lower in WT-22Rv1, than in AMC-22Rv1 and RR-22Rv1 cells.…”
Section: Discussionmentioning
confidence: 92%
“…The NRF2 increased expression following TT is related to improved conditions of oxidative stress through reduced production of reactive oxygen species (Cheung et al, ). In prostate tumor cells, NRF2 up‐regulation is able to inhibit proliferation and invasion (Liu et al, ; Li et al, ), and becomes a new promising target for treating prostate cancer (Xue et al, ).…”
Section: Discussionmentioning
confidence: 99%